2007
DOI: 10.1007/s11010-007-9686-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of ACE/AT2R complex in the control of mesenteric resistance artery contraction induced by ACE/AT1R complex activation in response to Ang I

Abstract: Objectives-In this study we will determine the function of the interaction between AT 2 R and ACE, and AT 1 R and ACE in the control of mesenteric resistance artery (MRA) tone from normotensive and Angiotensin II (AII)-dependent hypertensive mice.Methods-results-Hypertension (HT) was induced by infusion of Ang-II (200ng/kg/day) for 3 weeks. Freshly MRA (100-120μm) were isolated from HT and normotensive (NT) mice and mounted in an arteriograph. Dose-response of Ang-I induced a similar contraction of MRA from NT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(31 reference statements)
3
3
0
Order By: Relevance
“…Employing rat adrenal medulla as the positive control for AT2R antibody, we obtained a distinct band at 50~ kDa (blot 5, Figure 5). This molecular weight is consistent with Abcam datasheet (http://www.abcam.com/Angiotensin-II-Type-2-Receptor-antibody-ab78747.pdf), and published data by other groups using AT2R antibody from Cell Signaling Technology 70 or from Santa Cruz Biotechnology 71 , and our previous results by AT2R antibody from Santa Cruz Biotechnology (sc-9040) 11 , which is another rigorously validated, well-characterized AT2R antibody 72 . The AT1R has a calculated mass of 40,889 Daltons as deduced from its 359 amino acid sequence 73;74 and the molecular mass of AT2R is predicated to be 41,346 Daltons based on its 363 amino acid sequence 75;76 .…”
Section: Discussionsupporting
confidence: 90%
“…Employing rat adrenal medulla as the positive control for AT2R antibody, we obtained a distinct band at 50~ kDa (blot 5, Figure 5). This molecular weight is consistent with Abcam datasheet (http://www.abcam.com/Angiotensin-II-Type-2-Receptor-antibody-ab78747.pdf), and published data by other groups using AT2R antibody from Cell Signaling Technology 70 or from Santa Cruz Biotechnology 71 , and our previous results by AT2R antibody from Santa Cruz Biotechnology (sc-9040) 11 , which is another rigorously validated, well-characterized AT2R antibody 72 . The AT1R has a calculated mass of 40,889 Daltons as deduced from its 359 amino acid sequence 73;74 and the molecular mass of AT2R is predicated to be 41,346 Daltons based on its 363 amino acid sequence 75;76 .…”
Section: Discussionsupporting
confidence: 90%
“…However, the TDA exhibited a low response to Ang II compared with the other vasoconstrictors discussed above; indeed, the maximum effect for Ang II was approximately 70% of the maximal diameter, whereas all the other vasoconstrictors induced a maximum effect between 30 and 40% of the maximal diameter. However, this observation has also been reported in several papers in the second and third order of mesenteric artery [35,42,54,67]. Altogether, these results demonstrate that the TDA exhibits similar responses to contractile agents compared to those reported in the extensively studied mesenteric arteries, which makes the TDA an adequate vascular model system for vasoreactivity studies.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, it has been reported that Ang II increases vasoconstriction partially through O 2 •− -induced inactivation of vasorelaxant NO 1 , although this response depends on vascular-bed and genetic background. 25, 26 In the present study, we found that contractions to the Ang II, but not KCl, are significantly increased in mesenteric arteries of the Atox1 −/− mice compared with WT mice. This is inhibited by SOD mimetic tempol.…”
Section: Discussionsupporting
confidence: 50%